Predictors of paravalvular aortic regurgitation following self-expanding Medtronic CoreValve implantation: The role of annulus size, degree of calcification, and balloon size during pre-implantation valvuloplasty and implant depth. (20th January 2015) - Ali, O.F.; Schultz, C.; Jabbour, A.; Rubens, M.; Mittal, T.; Mohiaddin, R.; Davies, S.; Di Mario, C.; Van der Boon, R.; Ahmad, A.S.; Amrani, M.; Moat, N.; et al.
Abstract: Objectives: We sought to investigate the role of balloon size during pre-implantation valvuloplasty in predicting AR and optimal Medtronic CoreValve (MCS) implantation depth. Background: Paravalvular aortic regurgitation (AR) is common following MCS implantation. A number of anatomical and procedural variables have been proposed as determinants of AR including degree of valve calcification, valve undersizing and implantation depth. Methods: We conducted a multicenter retrospective analysis of 282 patients who had undergone MCS implantation with prior cardiac CT annular sizing between 2007 and 2011. Native valve minimum (Dmin), maximum (Dmax) and arithmetic mean (Dmean) annulus diameters as well as agatston calcium score were recorded. Nominal and achieved balloon size was also recorded. AR was assessed using contrast angiography at the end of each procedure. Implant depth was measured as the mean distance from the nadir of the non- and left coronary sinuses to the distal valve frame angiographically. Results: 29 mm and 26 mm MCS were implanted in 60% and 39% of patients respectively. The majority of patients (N = 165) developed AR < 2 following MCS implantation. AR ≥ 3 was observed in 16% of the study population. High agatston calcium score and Dmean were found to be independent predictors of AR ≥ 3 in multivariate analysis ( P  < 0.0001). Nominal balloon diameter and the number of balloon inflations did not influence AR. However a small achieved balloon diameter-to-Dmean ratio (≤ 0.85) showed modest correlation with AR ≥ 3 ( P  = 0.04). This observation was made irrespective of the degree of valve calcification. A small MCS size-to-Dmean ratio is also associated with AR ≥ 3 ( P  = 0.001). A mean implantation depth of ≥ 8 + 2 mm was also associated with AR ≥ 3. Implantation depth of ≥ 12 mm was associated with small MCS diameter-to-Dmean ratio and increased 30-day mortality. Conclusion: CT measured aortic annulus diameter and agatston calcium score remain important predictors of significant AR. Other procedural predictors include valve undersizing and low implantation depth. A small achieved balloon diameter-to-Dmean ratio might also predict AR ≥ 3. Our findings confirm that a small achieved balloon size during pre-implantation valvuloplasty predicts moderate–severe AR in addition to previously documented factors.